XRCC2 and XRCC3 Gene Polymorphism and Risk of Pancreatic Cancer - Jiao, Li (2007)
OBJECTIVES: XRCC2 and XRCC3 are key components of the homologous recombination (HR) machinery that repairs DNA double-strand breaks. We hypothesized that the altered HR repair capacity conferred by single nucleotide polymorphisms (SNPs) would modify individual susceptibility to sporadic pancreatic cancer. METHODS: In a hospital-based case-control study, genomic DNA and exposure information was obtained from 468 patients with pathologically confirmed pancreatic adenocarcinoma and 498 frequency-matched healthy controls at M.D. Anderson Cancer Center during January 2000 to September 2006. Genotypes of XRCC2 31479 G>A (Arg(188)His) and XRCC3 17893 A>G and 18067 C>T (Thr(241)Met) were determined using the Masscode technology. Unconditional logistic regression models were used to estimate the odds ratio (OR) and its 95% confidence interval (CI) in non-Hispanic whites (408 cases and 449 controls). RESULTS: The distribution of genotype frequencies was not different between cases and controls. We observed a significant effect modification between XRCC2 polymorphism and smoking status and pack-year of smoking in modifying pancreatic cancer risk (P value for interaction 0.02 and 0.05, respectively). Compared with never-smokers carrying the XRCC2 Arg(188)Arg genotype, the OR (95% CI) for individuals carrying the (188)His allele was 2.32 (1.25-4.31) among ever-smokers, 1.43 (0.59-3.48) among light smokers (<22 pack-years), and 3.42 (1.47-7.96) among heavy smokers (≥22 pack-years). The two XRCC3 SNPs are in strong linkage disequilibrium, but there was no suggestive association between XRCC3 genotype and the risk of pancreatic cancer. CONCLUSION: XRCC2 Arg(188)His polymorphism may be one of the genetic modifiers for smoking-related pancreatic cancer.